Research the process of informal socialization in human-animal groups - Miljutina, K. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2018)
There is a problem of the theoretical models development of the process of informal socialization study. Both the factors and the effects on the individual of such a process of socialization should be investigated. Peculiarity of the informal socialization is subjective activity of an individual, his independent choice of his own path of self-development and his way of rest. Factors can be classified into external, internal and situational. Informal socialization effects may be changes in the emotional sphere of personality. The external factors of informal socialization may include availability of free time and energy, which makes it possible to be engaged in some form of informal activity. Habitat and its conditions can also affect the process, the availability of resources for informal education, socialization and so on in a big city is more than in towns and villages. The article is devoted determination of concept and tipological variants of informal socialization and empiric research of this phenomenon on the example of intercourse in groups. It was discovered that level of satisfaction by life and social support more high for persons which were the successful and responsible proprietors of pets. The system of factors of informal socialization and prospect of its research is considered.